Księgi kostiumów jako interpretacja i symboliczna wykładnia świata w XVI-wiecznej Europie - Szymankiewicz, Karolina (Załącznik Kulturoznawczy, 2022)
This article aims to present sixteenth-century costume books as a phenomenon that was one of the ways of getting to know the world in the modern era (both in micro and macro perspective), accompanied by emphasizing and even exaggerating features and elements of appearance considered to be characteristic of given societies. In order to characterize this phenomenon in detail, the genesis, function and reasons for the popularity of costume books are also given. The text also includes their interpretation in the broader context of socio-cultural changes taking place in 16th-century Europe – these collections of representations were the European visualization of time and space, however they did not reflect reality, but created the way the world was perceived by the use of non-obvious means. They made it possible to show in a compact collection a large number of images of representatives of various nations in clothes typical for a particular region of the world, in a way making it symbolically smaller and more accessible. For this reason, it is possible to point out analogies between the operation of costume books and Kunst- und Wunderkammer, which is emphasized in the article. Thus, these collections of representations can also be considered from the perspective of a specific kind of collecting – the collecting of human images (human types) through their appropriation. Therefore, one of the hypotheses presented in the article is to delineate the relationship between costume books and the centuries-long process of perpetuating the claim of colonialism in certain countries which took place not only in the political-economic sphere, but also in the field of visual arts.